Globalization and Its Impact on Education in Developing Countries - Pattila Puzhankara, Renuka Devi (INTI International University, 2009)
The term globalization has become controversial due to its ambiguous nature. Globalization in higher education and science is inevitable. Historically, academe has always been international in scope, and it has always been characterized by inequalities. Modern technology, the Internet, the increasing ease of communication, and the flow of students and highly educated personnel across borders enhances globalization. No academic system can exist by itself in the 21st century. The challenge is to recognize the complexities and nuances of the modern context and then seek to create a global academic environment that recognizes the need to ensure that academic relationships are as equal as possible. Recognizing inequality is the first step. The second is to create a world that ameliorates these inequalities. These tasks, in the context of globalization and the pressures of mass higher education, are not easy ones. Yet, it is important to ensure that globalization does not turn into the neocolonialism of the 21st century. My intention is to reveal some of the realities of globalization and internationalization in higher education and to highlight some of the ways in which globalization affects higher education in developing countries